Consumer responses and willingness-to-pay for hibiscus products: A preliminary study - Ndiaye, Oumoule; Hedrick, Valisa E.; Neill, Clinton L.; Carneiro, Renata C. V.; Huang, Haibo; Fernandez-Fraguas, Cristina; Guiro, Amadou Tidiane; O'Keefe, Sean F. (Frontiers in Sustainable Food Systems, 2023)
The rise in diseases like obesity and diabetes is a worldwide challenge. The consumption of functional products such as hibiscus, which has been proven to be high in bioactive compounds and dietary fiber, providing it with anticancer, antiaging, anti-inflammatory and satiety properties, should be promoted. In the U.S., promoting the consumption of hibiscus products can be a good approach to increase fiber consumption and to reduce risk of obesity, diabetes, and hypertension. However, information about knowledge of this functional product among consumers is still sparse and increasing consumption requires designing and marketing desired products made from hibiscus. Therefore in this preliminary study, we assessed consumer response to hibiscus products and investigated whether providing information about potential health benefits could impact consumer willingness-to-pay (WTP) for three types of non-alcoholic hibiscus beverages: ready-made tea, bottled juice, and kombucha. Our web-based survey was distributed through QualtricsXM and a convenience sampling method was chosen. Most participants identified themselves as female, 18–34 years old, with a graduate degree. Most participants (81%) had consumed hibiscus products before and 57% had a weekly food budget lower than 60. Overall, tea and juices were the most liked hibiscus beverages, respectively. Although taste and health benefits were ranked as the main reasons to consume hibiscus beverages, additional information about hibiscus health benefits did not significantly affect WTP for these products. Without additional health benefit information, consumer WTP for non-alcoholic hibiscus beverages ranged from 2.9 to 3.60 for kombucha and 4.08–4.97 for Ready-made-tea. This study provides valuable insights that can support future research on hibiscus products and promote the development of novel hibiscus-based foods and beverages that are appealing to the U.S. market.